Buckled AgNW/MXene hybrid hierarchical sponges for high-performance electromagnetic interference shielding. Issue 47 (21st November 2019) - Weng, Chuanxin; Wang, Guorui; Dai, Zhaohe; Pei, Yongmao; Liu, Luqi; Zhang, Zhong
Abstract : The development of electromagnetic interference (EMI) shielding materials is moving forward towards being lightweight and showing high-performance. Abstract : The development of electromagnetic interference (EMI) shielding materials is moving forward towards being lightweight and showing high-performance. Here, we report on lightweight silver nanowire (AgNW)/MXene hybrid sponges featuring hierarchical structures that are fabricated by a combination of dip-coating and unidirectional freeze-drying methods. The commercial melamine formaldehyde sponges (MF), designed with a buckled structure, are chosen as the template for coating with the AgNW layer (BMF/AgNW). Furthermore, the additional irregular honeycomb architecture composed of MXene assembled cell walls is introduced inside the BMF cell–matrix through unidirectional freeze-drying of MXene aqueous suspensions. Consequently, the BMF/AgNW presents a better EMI shielding effectiveness of 40.0 dB contributed by the conductive network and multiple reflections and scattering compared with the MF/AgNW. Eventually, the resulting AgNW/MXene hybrid sponge exhibits a higher EMI shielding effectiveness of 52.6 dB with a low density of 49.5 mg cm −3 compared with the BMF/AgNW due to synergetic effects of the AgNW and MXene both in conductivity and hierarchical structure. These results also provide a novel way to fabricate lightweight and conductive sponges as high-performance EMI shielding materials.